Steamboat WHITE HORSE at Five Finger Rapids on the Yukon River, Yukon Territory, ca. 1899. - Hamacher & Doody
PH Coll 246.188 The partnership of Hamacher & Doody was Edward J. Hamcher and Jeremiah Doody. [Meed journal: "Str. "White Horse". One of three sister vessels, the others being the "Selkirk" and the "Dawson". Owned by the White Pass & Yukon Railway Co. This one is coming upstream against the current aided by the steam capstan on the bow and a long steel-wire cable. The scene is at Five Finger Rapids." To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number